PENGARUH PEMBELAJARAN MATA KULIAH SEPAKBOLA TERHADAP PENINGKATAN TEKNIK DASAR SEPAKBOLA PADA MAHASISWA IKOR UNIMED 2023 - Dwi Yudistira, Galih; Nusri, Ardi; Mesnan, Mesnan; Mediyana Sari, Rima; Ratno, Puji (JURNAL ILMU KEOLAHRAGAAN, 2024)
This research aims to determine the effect of learning football courses on improving basic football techniques among IKOR Unimed 2023 students. The method used in the research is an experimental method with data collection techniques using tests and measurement tests using basic football technique tests. The sample of this study was 92 students of the Sports Science Department of Unimed in 2023. The data analysis technique in this study used the paired sample t-test, namely, the data analyzed were the initial test and the final test. The results of the study showed that based on the hypothesis test using the paired sample t-test with a value of 0.000 <0.05 there was a significant difference in the results of basic football techniques before and after treatment was given. It can be concluded that there is an effect of learning football courses on improving basic football techniques in IKOR Unimed 2023 students